The data-driven blockchain ecosystem : fundamentals, applications, and emerging technologies - Khang, Alex; Chowdhury, Subrata; Sharma, Seema, (Computer scientist) (Boca Raton, FL : CRC Press, 2022)
"Data-Driven Blockchain Ecosystem: Fundamentals, Applications, and Emerging Technologies discusses how to implement and manage processes for releasing and delivering blockchain applications. It presents the core of blockchain technology, IoT-based, and AI-based blockchain systems, and various manufacturing areas of Industry 4.0. The book illustrates how to apply design principles for the development activities and managing blockchain networks and also covers the role that cloud computing plays with blockchain applications"--
Comprehensive analysis of fundamentals, innovation and key challenges of blockchain / Mukesh Soni, Mohamed A. Elashiri, Abdulah S. Almahayreh, Abdelwahab Said Hassan -- Cryptocurrency methodologies and techniques / S. Hasan Hussain, T. B. Sivakumar -- Framework for modelling, procuring, and building systems for smart city scenarios using blockchain technology and IoT / Rajendra Kumar, Ram Chandra Singh, Rohit Khokher.
OCLC-licensed vendor bibliographic record.
Keywords: Blockchains (Databases); TECHNOLOGY / Manufacturing; TECHNOLOGY / Operations Research